(NaKTERSKOE MASTERSTWOs (NMETODIKA(B.(Nu^EBNOE POSOBIEs - (Nm(B.(Ne(B.(NaLEKSANDROWAs ((NsANKT(B-(NpETERBURGs (NlANXs (NpLANETA MUZYKIs, 2023)
(NkNIGA TEATRALXNOGO REVISSERA mARII aLEKSANDROWOJ aKTERSKOE MASTERSTWO(B.s
Keywords: (NmETODIKAs